RE-ACTUALIZATION OF PANCASILA VALUES ON LAW ESTABLISHMENT IN THE ECONOMIC GLOBALIZATION ERA - Ninuk Triyanti (UNISSULA, 2019)
Economic globalization which is characterized by the strengthening of capitalist liberalism greatly influences the legal order in Indonesia, so that much national legislation is found in the economic field that is loaded with capitalist liberals that do not reflect the values of the Pancasila. This research is intended to explain the importance of re-actualizing the Pancasila values and how to re-actualize the Pancasila values in the formation of laws in the economic field. The results showed that the re-actualization of the values of Pancasila n the formation of laws was an important requirement and as a means to achieve the goals of the country, namely to realize the welfare of the people. The method of actualizing Pancasila values in the formation of laws is carried out through 4 (four) stages in the process of forming laws, namely through the stages of planning the law, the stage of drafting the bill, the stage of discussion of the bill and the stage of ratification of the bill into law.